Livelihood Safety And Safeguards In Agriculture (Texas Journal of Engineering and Technology, 2024)
It is necessary to observe the safety of life activity in the planting and care of each type of crop in agriculture, and it is necessary to ensure human safety not only in agriculture, but also in processing enterprises